(untitled) (Revista de Ensino em Artes, Moda e Design, 2024)
Contemporary times are marked by issues that lead us to the emergence of environmental concerns, pointing towards challenges where the aspirations and hopes of civilization for the future are embedded. In this economic scenario, industrial society is characterized as the means to provide consumer subjects with all the material and informational structure they may need throughout their life cycle in a specific historical, technological, and cultural context. In contrast, the "environment" is an integral part of the physical space necessary for the survival and interactions of humans and all forms of life on the planet. For designers, the environment should be considered as a system of artifacts and structures capable of interrelating harmoniously with the physical and natural environment, ensuring balanced use, maintenance, and preservation of resources. This article aims to report the teaching experience in Fashion Design and its integration with other students at “Universidade Positivo” in an Institutional Extension Project related to the Applied Research to the Environment line, in cooperation with companies in the productive sector of the women’s clothing segment based on the scope of the “National Solid Waste Policy". Research and extension projects, mediated by the interdisciplinary vision of Design, spanning multiple areas of knowledge, provide opportunities for learning through dialogical interaction between the university and the community. They offer the potential for producing innovative and transformative knowledge in social, economic, technological, or environmental contexts, with a focus on issues related to fashion, sustainable development, and circular economy. A contemporaneidade é marcada por temas que nos reportam à emergência das questões ambientais e apontam para desafios, nos quais estão depositados os anseios e as esperanças da civilização. A sociedade industrial fornece aos sujeitos consumidores toda a estrutura material e informativa de que ele possa necessitar ao longo de seu ciclo de vida, em um determinado contexto histórico, tecnológico e cultural. Por outro lado, o meio ambiente é parte integrante do espaço físico necessário para a sobrevivência e interações dos seres humanos e todo o tipo de vida no planeta. Para o designer, o ambiente deveria ser considerado com um sistema de artefatos e estruturas capaz de se inter-relacionar em harmonia com o ambiente físico e natural, no uso, manutenção e preservação dos recursos de forma equilibrada. Este artigo pretende relatar a experiência de ensino em Design de Moda e a integração com outros estudantes da Universidade Positivo em um Projeto de Extensão Institucional relacionado à linha de Pesquisa Aplicada ao Meio Ambiente, em cooperação com empresas do setor produtivo do segmento de vestuário feminino, a partir do escopo da Política Nacional de Resíduos Sólidos (PNRS). Os projetos de pesquisa e extensão mediados pela visão interdisciplinar do Design, ao abranger múltiplas áreas do conhecimento, oferecem a oportunidade de aprendizado, por meio da interação dialógica entre universidade e comunidade, com a possibilidade da produção de conhecimentos com potencial inovador e transformador de contexto social, econômico, tecnológico ou ambiental, com destaque às questões relacionadas à moda, desenvolvimento sustentável e economia circular.